Pengembangan Alat Timbangan Digital Berbasis Arduino Nano dan Desain Kemasan untuk Meningkatkan Kualitas Produk UMKM Bubuk Jahe Bu Mai - Dicky Syahrul Nizam; Virgi Senalia Hamidah; Ika Ayu Nurlela; Febrianti C.P.N; M.Rio Sihabuddin (Maisyatuna, 2025)
This research aims to develop a digital weighing scale based on Arduino Nano that can be used to accurately measure the weight of products in micro, small,and medium enterprises (MSMEs) producing ginger powder, specifically for the MSME "Bubuk Jahe Bu Mai." Additionally, this research also includes the design of attractive and practical packaging to enhance the product's appeal in the market. The implementation of this digital weighing scale is expected to improve efficiency in the production process and ensure product weight consistency, while the packaging design aims to attract consumers' attention and enhance the product's image. The method used is research and development (R&D) with a product design approach and tool testing. The results of this research show that the developed digital weighing scale can produce accurate measurements with a very small margin of error. The packaging design also successfully improved the product's presentation, which can attract consumers' attention. The implementation of these two components is expected to improve the quality of "Bubuk Jahe Bu Mai" products and provide a positive impact on the product's competitiveness in the market.